PTU-255 Characterisation of drug transporter gene expression in colorectal tissue and cell lines: induction with anti-retrovirals for microbicide optimisation. (22nd June 2015) - Mukhopadhya, I; Berry, S; Thomson, J; Murray, GI; El-Omar, EM; Hold, GL; Hijazi, K
Abstract : Introduction: Drug transporter expression in the colorectal epithelium is likely to play a role in the mucosal disposition of anti-retrovirals (ARVs) in rectal microbicidal preparations and impact their efficacy in prevention of HIV-1 infection. However, there is limited information on expression levels available. This study aims to assess expression of 84 drug transporter genes in human colorectal tissue and representative cell lines pre and post ARV exposure. Method: Drug transporter mRNA expression was quantified from colorectal biopsies (n = 12) and 6 colorectal cell lines using real time PCR. Relative mRNA expression was quantified in Caco-2 cells after induction with tenofovir (TFV; 5 mM), dapivirine (DPV; 10 µM) and darunavir (DRV; 250 µM) for up to 3 days. Data were analysed using Pearson's correlation (r), hierarchical clustering and principal component analysis. Results: Fifty-eight of the 84 transporters were expressed in colorectal tissue. SLC28A2/CNT2 was the most expressed uptake transporter (>25 fold increase) followed by efflux transporters ABCB1/P-gp and ABCC3/MRP3 (4–5 fold increase). No difference was noted between individual patients, either sexes or biopsy sites (rectum or sigmoid) (r = 0.95–0.99). Similarities between tissue and cell lines were low (r values 0.67–0.81). Principal component analysis showed distinct clustering of colorectal tissue and cell lines with Caco-2 cells showing least variance with tissues. Immunohistochemical staining of 7 colorectal biopsy sections confirmed high expression of Pgp and CNT2 drug transporters. TFV stimulation of Caco-2 cells resulted in > 2 fold increase in expression of MRP5, LAT2, OATPE and GLUT1 mRNA. DPV stimulation resulted in > 2 fold increase in expression of GLUT1, PEPT1 and ABCA1. DRV stimulation resulted in > 2 fold increase in expression of SLC3A2, OATPE and MCT3 mRNA. Conclusion: This study has enumerated drug transporter mRNA expression in colorectal tissue and cell lines. There was partial correlation between cell lines and tissue limiting cell line use as in vivo surrogate. TFV and DPV did not induce majority of efflux transporters in Caco-2 cells. This would entail increased retention of drug within the mucosa and as a result enhanced delivery to CD4 T cells. Further studies will elucidate whether combination of ARVs will be similarly effective. Disclosure of interest: None Declared.